Assimilation of Piano Learning through the Integration of Technique, Theory, and Technology - Mauassa, Teguh Yusuf Vertian; Wadiyo, Wadiyo; Sinaga, Syahrul Syah (Riwayat: Educational Journal of History and Humanities, 2025)
The process of learning the piano involves more than the acquisition of technical skills; it also encompasses theoretical understanding, aesthetic appreciation, and adaptation to individual learner needs. This literature review examines the assimilation of piano learning through the integration of technique, theory, and technology, synthesizing findings from ten recent academic studies. The analysis reveals that effective assimilation occurs across five key dimensions: (1) multidimensional integration of technical proficiency, theoretical knowledge, and artistic expression; (2) combination of multiple memory strategies, including aural, visual, kinesthetic, and analytical approaches; (3) adaptation of teaching methods for learners with special needs; (4) interdisciplinary collaboration between music pedagogy and related sciences such as biomechanics; and (5) incorporation of technological innovations, ranging from adaptive visualisation tools to passive haptic rehearsal devices. The findings highlight that assimilation in piano learning is a dynamic, creative, and adaptive process that bridges traditional pedagogy with modern advancements. This integrated approach not only enhances skill acquisition but also fosters a deeper, more sustainable engagement with music. Future research is recommended to explore how these dimensions can be optimized simultaneously to achieve more inclusive and effective piano learning outcomes.